Posterior Cerebellar Volume and Executive Function in Young Adults With Congenital Heart Disease. (30th May 2018) - Semmel, Eric S.; Dotson, Vonetta M.; Burns, Thomas G.; Mahle, William T.; King, Tricia Z.
Abstract: Objectives: As the number of adolescents and young adults (AYAs) surviving congenital heart disease (CHD) grows, studies of long-term outcomes are needed. CHD research documents poor executive function (EF) and cerebellum (CB) abnormalities in children. We examined whether AYAs with CHD exhibit reduced EF and CB volumes. We hypothesized a double dissociation such that the posterior CB is related to EF while the anterior CB is related to motor function. We also investigated whether the CB contributes to EF above and beyond processing speed.Methods: Twenty-two AYAs with CHD and 22 matched healthy controls underwent magnetic resonance imaging and assessment of EF, processing speed, and motor function. Volumetric data were calculated using a cerebellar atlas (SUIT) developed for SPM. Group differences were compared with t tests, relationships were tested with Pearson's correlations and Fisher's r to z transformation, and hierarchical regression was used to test the CB's unique contributions to EF.Results: CHD patients had reduced CB total, lobular, and white matter volume ( d =.52–.99) and poorer EF ( d =.79–1.01) compared to controls. Significant correlations between the posterior CB and EF ( r =.29–.48) were identified but there were no relationships between the anterior CB and motor function nor EF. The posterior CB predicted EF above and beyond processing speed ( p s<.001).Conclusions: This study identified a relationship between the posterior CB and EF, which appears to be particularly important for inhibitory processes and abstract reasoning. The unique CB contribution to EF above and beyond processing speed alone warrants further study. ( JINS, 2018, 24, 939–948)